Understanding the impact of attitudes toward seeking psychological help and school well-being on depression and anxiety among Vietnamese university students - Le Minh Cong; Nguyen Van Tuong; Nguyen Vu Thanh Tam (Discover Social Science and Health)
Abstract University students face significant mental health challenges, with high rates of depression and anxiety, particularly in Vietnam. Despite these concerns, many students are reluctant to seek psychological help due to stigma and lack of awareness. This study examines the relationship between attitudes toward seeking professional psychological help, school well-being, and mental health outcomes among Vietnamese university students. A cross-sectional survey of 8383 students was conducted using validated self-report measures, and data were analyzed through Partial Least Squares Structural Equation Modeling (PLS-SEM). Results showed that school well-being was negatively associated with depression and anxiety, suggesting that students with greater school satisfaction had better mental health. Open-mindedness and belief in professional help were also negatively related to mental distress. However, higher awareness of psychological issues was positively associated with depression and anxiety, indicating that awareness alone may not reduce mental health risks. These findings emphasize the need for universities to foster supportive environments, reduce stigma, and implement culturally appropriate mental health programs to encourage professional help-seeking and improve student well-being.